Aptitude Overflow

–1 vote

Given the quadratic equation $x^{2}-(A-3) x- (A-2) = 0$, for what value of $A$ will the sum of the squares of the roots be zero?

- $-2$
- $3$
- $6$
- None of these

+1 vote

Best answer

Let the two roots be $\alpha _{1}$ and $\alpha _{2}$

For a quadratic equation $ax^2 +bx +c = 0$, sum of the roots $= -\frac{b}{a}$ and product of the roots $=\frac{c}{a}.$So,

$\alpha _{1}$ + $\alpha _{2}$ = (A - 3)

$\alpha _{1}$.$\alpha _{2}$ = -(A - 2)

We want $\alpha _{1}^{2}$ + $\alpha _{2}^{2}$ = 0

$\Rightarrow$ $\left ( \alpha _{1} + \alpha _{2} \right )^{2}$ - 2$\alpha _{1}$.$\alpha _{2}$ = 0

$\Rightarrow$ (A - 3)^{2} - 2(-(A - 2)) = 0

$\Rightarrow$ A^{2} - 4A + 5 = 0

$\Rightarrow$ A = 2 $\pm$ i

**D is the answer**

2,807 questions

1,171 answers

431 comments

40,049 users